Penyuluhan Program Penghijauan untuk Menanamkan Pendidikan Karakter "Cinta Lingkungan" di Sekolah Dasar - Dewi Masithoh; Riska Anintyawati (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2022)
The importance of maintaining the environment so that the earth remains sustainable, efforts need to be made to develop character education "Love the Environment" for elementary school residents and train students to form individuals who care about the surrounding natural environment through greening programs. This program is carried out in the neighborhood around MI Al-Mumtaz Pathuk, Gunungkidul, Yogyakarta. It consists of several stages, namely character education counseling, gardenization programs, and reading garden spots. The series of program implementations were carried out well for six months from October 2020 to March 2021. The result of this activity is to educate the importance of preserving the environment, increase awareness of the importance of protecting the environment, form a positive character "Love the Environment" in students and school residents.